ENHANCING LITERARY ANALYSIS SKILLS THROUGH AI-POWERED READING APPS: A CASE STUDY ON ENGLISH LITERATURE STUDENTS (INTERNATIONAL SEMINAR, 2024)
This study examines the impact of AI-poweredreading applications on the literary analysis skills of EnglishLiterature students. With the increasing integration ofartificial intelligence in educational technology, thesereading apps offer a range of interactive features that maysupport students in interpreting and analyzing texts. Usinga qualitative case study approach, this research involved 10-15 students who regularly use AI-powered reading apps.Data was collected through semi-structured interviews,observations, and analysis of students’ work, focusing ontheir engagement with app features that support criticalreading and analysis. The findings reveal the ways AIdriven features—such as interactive annotations, contextualsummaries, and analytical prompts—help students improvetheir interpretive skills. Additionally, this study highlightschallenges, including over-reliance on automatedinterpretations and occasional limitations in app-generatedinsights. The results contribute valuable insights foreducators seeking to integrate AI-driven tools in literatureeducation and suggest practical recommendations forenhancing students' analytical proficiency throughtechnology.